Molecular identification of methicillin resistance and virulence marker in Staphylococcus aureus - ND Gunawardena (Sri Lankan Journal of Infectious Diseases, 2012)
Methicillin-Resistant Staphylococcus aureus (MRSA) is one of the major nosocomial pathogens in Sri Lanka. Life threatening infections with MRSA require rapid identification in order to initiate appropriate antimicrobial therapy. The Panton- Valentine leukocidin (PVL) is a virulence factor associated with severe MRSA infections for which routine detection is time consuming and dependent on the culture environment.1 The current study was therefore carried out to develop a rapid method for detection of MRSA and the presence of PVL gene using a multiplex polymerase chain reaction (mPCR). In the first phase of this study, results of conventional and molecular methods were compared for 43 clinical isolates of Staphylococcus aureus received from Teaching Hospital Peradeniya (THP). In the second phase, an additional 43 clinical samples obtained from patients were directly tested using mPCR and results including detection time of conventional and molecular methods compared. femB was negative in 7 of 43 isolates identified as S aureus by conventional methods. Of the remaining 36 isolates, 12 were mecA positive with an oxacillin MIC of >2mg/L. The mecA gene was detected in 10 isolates identified as MSSA by conventional testing. The PVL gene was detected in 11 strains including both MRSA and MSSA. Direct mPCR on clinical samples was negative for all 3 genes in 15 of 43 samples from which S aureus was isolated. Of the remaining 28 samples, 24 were femB positive, 16 were mecA positive and 14 were positive for the PVL gene. mPCR is helpful for the rapid identification of methicillin resistance and PVL production is staphylococci but less helpful in direct testing of samples. DOI: http://dx.doi.org/10.4038/sljid.v2i2.4303 Sri Lankan Journal of Infectious Diseases Vol.2(2) 2012: 18-29